Application and multidisciplinary aspects of wireless sensor networks : concepts, integration, and case studies - Gavrilovska, Liljana (Computer communications and networks, 2011)
This hands-on introduction to WSN systems development covers a broad range of topics in the field, with contributions from researchers involved in the ProSense project. It emphasizes the practical knowledge required for the successful implementation of WSNs